New Method for Hydraulic Characterization of Variably Saturated Zone in Peatland-Dominated Permafrost Mires - Radhakrishna Bangalore Lakshmiprasad; Stephan Peth; Susanne K. Woche; Thomas Graf (Land)
Modeling peatland hydraulic processes in cold regions requires defining near-surface hydraulic parameters. The current study aims to determine the soil freezing and water characteristic curve parameters for organic soils from peatland-dominated permafrost mires. The three research objectives are as follows: (i) Setting up an in situ soil freezing characteristic curve experiment by installing sensors for measuring volumetric water content and temperature in Storflaket mire, Abisko region, Sweden; (ii) Conducting laboratory evaporation experiments and inverse numerical modeling to determine soil water characteristic curve parameters and comparing three soil water characteristic curve models to the laboratory data; (iii) Deriving a relationship between soil freezing and water characteristic curves and optimizing this equation with sensor data from (i). A long-lasting in situ volumetric water content station has been successfully set up in sub-Arctic Sweden. The soil water characteristic curve experiments showed that bimodality also exists for the investigated peat soils. The optimization results of the bimodal relationship showed excellent agreement with the soil freezing cycle measurements. To the best of our knowledge, this is one of the first studies to establish and test bimodality for frozen peat soils. The estimated hydraulic parameters could be used to better simulate permafrost dynamics in peat soils.